Anti-dengue viral activity of Glycyrrhiza glabra roots in Vero cells - Kalani Gayathri Jayasekara; Sugandhika Suresh; Charitha Goonasekara; Preethi Soyza; Namal Perera; Kamani Gunasekera (Scientific Reports, 2024)
Abstract Despite being a global public health problem, there are no antiviral agents for dengue. Plants are the sources of most approved drugs and many phytochemicals have exhibited in vitro antiviral activity. We explored the antiviral potential of the aqueous extract of Glycyrrhiza glabra roots (GGaq) on dengue viruses. Plaque reduction antiviral assay for half maximal inhibitory concentrations (IC50) was done in Vero cells infected with dengue serotypes 1–4 and exposed to varying concentrations of GGaq. Half-maximal cytotoxic concentration (CC50) of the GGaq was 651.9 µg/mL. The IC50 of the four dengue serotypes (10–50 µg/mL) indicated moderate inhibition by GGaq. 98–100% inhibition of all dengue serotypes was seen with GGaq at the maximum nontoxic dose. Preparative thin layer chromatography of GGaq, isolated sub fractions E and F which had low to moderate antiviral activity (IC50 12.65–85.95 and IC50 13.14–69.27 respectively). They exhibited good therapeutic potential only for dengue serotype-4. Virus adsorption to cells was significantly inhibited by GG (50%) and sub fraction E (24.9%). Chloroquine diphosphate was used as the positive control in all assays. The aqueous extract of GG was non-toxic and had better antiviral activity than sub fractions E and F.